A novel herbal composition containing extracts of Boswellia serrata gum resin and Aegle marmelos fruit alleviates symptoms of asthma in a placebo controlled double‐blind clinical study. (6th December 2017) - Yugandhar, Pothina; Rao, Konda Manikyeswara; Sengupta, Krishanu
Abstract : LI13109F is a novel herbal composition containing the extracts of Boswellia serrata gum resin and Aegle marmelos fruit. This composition dampens leukotriene dependent inflammatory reactions via inhibiting 5‐lipoxygenase pathway. In a Sephadex LH‐20 induced airway inflammation model of Sprague Dawley rats, LI13109F significantly reduced infiltrated granulocyte population in the bronco‐alveolar lavage fluid and normalized Th1/Th2 cytokine balance. Further, a 56‐day placebo‐controlled and randomized double blind study (Clinical Trial Registration No. CTRI/2016/10/007393) on subjects with mild to moderate asthma has evaluated the clinical efficacy of LI13109F. The study subjects received either 200 mg/day of LI13109F ( n  = 18) or a similar dosage of placebo ( n  = 18). At the end of the trial period, LI13109F conferred significant improvements in the clinical parameters; the emotional function ( p  = .0305) and asthma symptoms scores ( p  = .0002) were improved even at 14 days, compared with the placebo. Further, 56 days supplementation of LI13109F resulted in significant increase in serum IFN‐γ ( p  = .0014) and reduction in IL‐4 ( p  = .0497), compared with placebo. LI13109F supplementation did not yield any serious adverse events or any abnormal observations in routine laboratory examinations during the study. Together, these observations suggest that LI13109F (AlvioLife®) is tolerable and an effective intervention for management of mild to moderate asthma such as airway inflammation.